Odpowiedzi

Najlepsza Odpowiedź!
2009-11-23T17:51:08+01:00
A. (x+2) (y+1)
xy+x+2y+2

b. (2a+1) (3-b)
6a-2ab+3-b

c. (a-1) (a²-b²)
a³-ab²-a²+b²

d. (2x-1) (y-3)
2xy-6x-y+3

e. (x-y) (a-b+9)
ax-bx+9x-ay+by-9y

f. (k²-2k+2) (t +8)
k²t-2kt+2t+8k²-16k+16
1 5 1
  • Użytkownik Zadane
2009-11-23T18:03:31+01:00
A. (x+2) (y+1) = xy+x+2y+2
b. (2a+1) (3-b) = 6a+2ab+3-b
c. (a-1) (a²-b²) = a³-ab²-a²+b²
d. (2x-1) (y-3) = 2xy-6x-y+3
e. (x-y) (a-b+9) = ax-bx+9x-ay+by-9y
f. (k²-2k+2) (t +8) = k²t-2kt+2t+8k²-16k+16
1 5 1